Ab initio molecular dynamics study of collective excitations in liquid H₂O and D₂O: Effect of dispersion corrections - Bryk, T.; Seitsonen, A.P. (Condensed Matter Physics, 2016)
The collective dynamics in liquid water is an active research topic experimentally, theoretically and via simulations. Here, ab initio molecular dynamics simulations are reported in heavy and ordinary water at temperature 323.15 K, or 50oC. The simulations in heavy water were performed both with and without dispersion corrections. We found that the dispersion correction (DFT-D3) changes the relaxation of density-density time correlation functions from a slow, typical of a supercooled state, to exponential decay behaviour of regular liquids. This implies an essential reduction of the melting point of ice in simulations with DFT-D3. Analysis of longitudinal (L) and transverse (T) current spectral functions allowed us to estimate the dispersions of acoustic and optic collective excitations and to observe the L-T mixing effect. The dispersion correction shifts the L and T optic (O) modes to lower frequencies and provides by almost thirty per cent smaller gap between the longest-wavelength LO and TO excitations, which can be a consequence of a larger effective high-frequency dielectric permittivity in simulations with dispersion corrections. Simulation in ordinary water with the dispersion correction results in frequencies of optic excitations higher than in D₂O, and in a long-wavelength LO-TO gap of 24 ps⁻¹ (127 cm⁻¹). Колективна динамiка у рiдкiй водi активно дослiджується експериментальними, теоретичними методами
та комп’ютерними симуляцiями. Представлено моделювання методом першопринципної молекулярної
динамiки для важкої та звичайної води при температурi 323.15 K, чи 50◦C. Моделювання для важкої води
були проведенi з та без дисперсiйних поправок. Ми отримали, що дисперсiйнi поправки (DFT-D3) суттєво змiнюють релаксацiю часових кореляцiйних функцiй густина-густина з повiльної, яка є типовою для
переохолодженого стану, до експоненцiйного спаду як для звичайних рiдин. Це означає суттєве зменшення точки плавлення льоду для моделювання з DFT-D3. Аналiз повздовжних (L) та поперечних (T)
спектральних функцiй потокiв дозволив визначити дисперсiї акустичних та оптичних збуджень та спостерiгати ефект L-T змiшування. Дисперсiйнi поправки D3 зсувають до нижчих частот L та T оптичнi (O)
моди та приводять до меншої на майже тридцять процентiв щiлини мiж LO та TO довгохвильовими збудженнями, що може бути наслiдком бiльшої високочастотної дiелектричної проникностi в моделюваннi
з дисперсiйними поправками. Моделювання для звичайної води з дисперсiйними поправками дає вищi
частоти оптичних збуджень, нiж для D₂O, та щiлину LO-TO порядку 24 пс⁻¹
(127 см⁻¹
) у довгохвильовiй
границi.